Minimally invasive surgery versus laparotomy in women with high risk endometrial cancer: A multi-center study performed in Argentina - Diego Odetto; Guido Martin Rey Valzacchi; Marcela Ostojich; Sebastian Alessandria; Maria Cecilia Darin; Karen Tapper; Alicia Rita Amato; Federico Luis Bianchi; Eduardo Fabian Lopresti; Lorena Soledad Cabrera; Jerónimo Costa; Agustín Esteban; et al. (Gynecologic Oncology Reports, 2023)
Objective: Compare the perioperative outcomes and disease-free survival between minimally invasive and open surgery in women with stage I–II high-risk endometrial cancer. Methods: A retrospective, cohort study was performed involving twenty-four centers from Argentina. Patients with grade 3 endometrioid, serous, clear cell, undifferentiated carcinoma or carcinosarcoma who underwent hysterectomy, bilateral salpingo-oophorectomy, and staging between January 2010–2018 were included. Cox hazard regression analysis and Kaplan-Meier curves evaluated the association of surgical technique with survival. Results: Of 343 eligible patients, 214 (62 %) underwent open surgery and 129 (38 %) underwent laparoscopic surgery. No significant differences were seen between the two groups with respect to greater or equal grade III Clavien-Dindo postoperative complications (11 % in the open surgery group vs 9 % minimally invasive surgery group; P = 0.34) Minimally invasive surgery was not associated with worse disease-free survival at four years (79.14 % [95 % CI 69.42– 86.08] vs 78.80 % [95 % CI 70.61–84.96]), (p = 0.25), even after creating a Cox proportional model (hazard ratio [HR] 1.08 95 % CI 0.63–1.84); (p = 0.76). Conclusion: There was no difference between postoperative complications nor oncologic outcomes comparing minimally invasive and open surgery among patients with high-risk endometrial cancer.